Mucocele of Appendix – Rare Entity –A Case Report - Shah, KZ; Begum, N; Khan, MMR; Ahmed, P; Vadro, SK (TAJ: Journal of Teachers Association, 2011)
Appendiceal mucocele (AM) is a rare entity that can present in a variety of clinical syndrome. The prevalence is 0.2- 0.4 % among appendicectomies.1 A 48 Years old male patient came to our Centre for Nuclear Medicine and Ultrasound (CNMU), Rajshahi for abdominal ultrasound examination. He had pain with vomiting and feeling of lumpiness in right side of lower abdomen. Ultrasonography (US) showed an elongated regular outlined semi-cystic lesion in right iliac fossa. Laparotomy done, per-operative finding reveled AM. Post-operatively histopathological examination report revealed AM. TAJ 2011; 24(1): 54-56